REPRESENTATION OF COMMUNICATION CRISIS IN THE FILM DON'T LOOK UP - Radya Putra, Firmansyah; Alrasid Ajibulloh, Alvian (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
A mass communication crisis occurs when the media fails to convey important information accurately, comprehensively, and responsibly to the public, especially in emergency situations. The film Don't Look Up (2021) provides a poignant representation of this phenomenon, presenting a critique of the failures of modern communication systems. This study aims to examine how the film represents the mass communication crisis through symbols, narratives, and visualizations of information conflict. The research method used is descriptive qualitative, with Roland Barthes's semiotic analysis technique and Stuart Hall's representation theory as theoretical foundations. The results show three main patterns of communication crisis: the rejection of science by political elites, media dysfunction in conveying critical messages, and the impact of disinformation on public polarization. The film highlights how communication crises stem not only from technical errors but are also influenced by socio-political structures that shape public opinion through biased and systemically politicized media.